Feasibility Study of Grounding Systems in the Dean's Building, Faculty of Engineering, Universitas Negeri Padang - Mursat, Marta Hardiyanti; Ta'ali, Ta’ali (Departemen Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2024)
This research aims to see the level of feasibility of the existing grounding system in the Dean's Building, Faculty of Engineering, Padang State University. The quality of the grounding can be seen from the measurement results using an Earth Tester. This is intended to see how the grounding system is installed in the dean building. After that, a feasibility study will also be carried out on the value of grounding installed in all engineering faculty dean buildings. A good grounding value should be between 0 and 5 Ω. In this study, the grounding value was measured using the HIOKI FT6031 Earth Tester measuring instrument with a three-point measurement method. This measurement is used to see whether the grounding system installed in the engineering faculty dean building complies with PUIL or not. The results of the research carried out can show that based on ground resistance measurements carried out directly in the Dean's Building, Faculty of Engineering, Padang State University, the measured values ​​do not meet the PUIL 2011 requirements for network systems. Apart from that, there is also a difference in the voltage value between the grounding value on the panel box and the voltage value on the first to fourth floors of the engineering faculty dean's building which is caused by a poor installation system